Recuperação de pastagem com estilosantes Campo Grande e adubação Fosfatada - Rebonatti, Melina Daniel [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The pasture is the basis of Brazilian livestock production, however, most pastures are degraded or in degradation process. In order to evaluate the recovery of degraded pasture Urochloa decumbens with introducing legume stylosanthes and phosphorus fertilization, an experiment was conducted in oxisol. The experimental design was a randomized block, 7x2x2 factorial scheme with four replications, involving seven managements introduction of stylosanthes (control Urochloa decumbens, partial desiccation with 1.5 L ha -1 of glyphosate, total desiccation with 3.0 L ha -1 of glyphosate; no tillage without dessication, soil scarification, harrowing, plowing+harrowing), presence or absence of phosphate fertilizer and two periods of evaluation (2011/12 and 2012/13). The introduction of stylosanthes Campo Grande through systems such as harrowing, scarification, and drying with phosphorus fertilization were not enough to keep the legumes in the pasture over time; the total dry mass was increased by dry mass production of stylosanthes; the phosphorus fertilization had an effect for dry matter production stylosanthes and total dry matter only in the spring / summer 2011/12; CP content of pasture was higher in the spring / summer of 1st period, when there was a high percentage of legumes in treatments with desiccation and soil disturbance; NDF and ADF contents were high in all treatments, especially in the autumn season; the introduction of stylosanthes in the pasture did not change the soil chemical properties; the phosphorus fertilization provided an increase of phosphorus and calcium in the soil, plus the sum of bases and cation exchange capacity

A pastagem é a base da produção pecuária brasileira, no entanto grande parte encontra-se degradada ou em processo de degradação. Com o objetivo de avaliar a recuperação de pastagem degradada de Urochloa decumbens através da introdução de estilosantes Campo Grande e da adubação fosfatada, realizou-se um experimento em Latossolo Vermelho Amarelo. O delineamento experimental foi em blocos casualizados, em esquema fatorial 7x2x2, com quatro repetições, sendo: sete manejos de introdução de estilosantes (controle Urochloa decumbens; dessecação parcial com 1,5 L ha -1 de glifosato; dessecação total com 3,0 L ha -1 de glifosato; plantio direto; escarificação; gradagem e aração+gradagem), presença ou ausência de adubação fosfatada e dois períodos de avaliação (2011/12 e 2012/13). A introdução do estilosantes Campo Grande através de sistemas como gradagem, escarificação, dessecação e juntamente com adubação fosfatada não foram manejos suficientes para manter a leguminosa na pastagem ao longo do tempo; a produção de massa seca total foi incrementada pela produção de massa seca do estilosantes; o adubo fosfatado apresentou efeito para produção de massa seca de estilosantes e total apenas na primavera de 2011/12; o teor de PB da pastagem foi maior na primavera/verão do 1o período; os teores de FDN e FDA foram elevados em todos os tratamentos, especialmente na estação do outono; a introdução do estilosantes na pastagem não alterou os atributos químicos do solo; a adubação fosfatada proporcionou aumento do teor de fósforo e cálcio do solo, além da soma de bases e capacidade de troca catiônica
Keywords: Forragem; Pastagens - Adubos e fertilizantes; Leguminosa; Cultivo consorciado; Forage